Learning allowed : children, communities and lifelong learning in a changing world - Frankel, Sam; Whalley, Caroline E. (Emerald Publishing Limited, 2023)
Nationally and internationally, we are being driven to reflect on how to respond to a changing world. Globally, the UN has presented its Sustainable Development Goals that include a commitment to the importance of learning (Goal 4). Considering what this means for the way we think about learning and how we see ourselves as learners, Learning Allowed builds a foundation for strengthening learner 'connectivity' whoever and wherever we are. Through an analysis of the existing discourses that have framed our approaches to education, Learning Allowed highlights a system that has lost touch with the individual and a desire to maximise learner potential, with implications for any lifelong motivations and ambitions for learning. In response to the myriad of technological, social, environmental and health changes, Learning Allowed presents a case for investing explicitly in a learner's sense of value, voice and vision in the context of a lifelong learning journey. Drawing on thinking from Childhood Studies and looking at its broader application in light of research from education studies, Frankel and Whalley focus on learner voice and participation, raising awareness about what learning is and how this is connected with emotional wellbeing, and the processes of learning. Learning Allowed acts as a catalyst to schools, homes and spaces beyond to reconsider notions of learning and the learner and look to re-present them.
Includes index.
Keywords: Education -- Philosophy.; Education, Philosophy, Theory & Social Aspects.; Philosophy & theory of education.; elektronické knihy; electronic books